Evolution of genomes, host shifts and the geographic spread of SARS-CoV and related coronaviruses - Janies, Daniel (2008)
Severe acute respiratory syndrome (SARS) is a novel human illness caused by a previously unrecognized coronavirus (CoV) termed SARS-CoV. There are conflicting reports on the animal reservoir of SARS-CoV. Many of the groups that argue carnivores are the original reservoir of SARS-CoV use a phylogeny to support their argument. However, the phylogenies in these studies often lack outgroup and rooting criteria necessary to determine the origins of SARS-CoV. Recently, SARS-CoV has been isolated from various species of Chiroptera from China (e.g., Rhinolophus sinicus) thus leading to reconsideration of the original reservoir of SARS-CoV. We evaluated the hypothesis that SARS-CoV isolated from Chiroptera are the original zoonotic source for SARS-CoV by sampling SARS-CoV and non-SARS-CoV from diverse hosts including Chiroptera, carnivores, artiodactyls and humans. Regardless of alignment parameters, optimality criteria, or isolate sampling, the resulting phylogenies clearly show that the SARS-CoV was transmitted to small carnivores well after the epidemic of SARS in humans that began in late 2002. The SARS-CoV isolates from small carnivores in Shenzhen markets form a terminal clade that emerged recently from within the radiation of human SARS-CoV. There is evidence of subsequent exchange of SARS-CoV between humans and carnivores. In addition SARS-CoV was transmitted independently from humans to farmed pigs (Sus scrofa). The position of SARS-CoV isolates from Chiroptera are basal to the SARS-CoV clade isolated from humans and carnivores. Although sequence data indicate that Chiroptera are a good candidate for the original reservoir of SARS-CoV, the structural biology of the spike protein of SARS-CoV isolated from Chiroptera suggests that these viruses are not able to interact with the human variant of the receptor of SARS-CoV, angiotensin-converting enzyme 2 (ACE2). In SARS-CoV study, both visually and statistically, labile genomic fragments and, putative key mutations of the spike protein that may be associated with host shifts. We display host shifts and candidate mutations on trees projected in virtual globes depicting the spread of SARS-CoV. These results suggest that more sampling of coronaviruses from diverse hosts, especially Chiroptera, carnivores and primates, will be required to understand the genomic and biochemical evolution of coronaviruses, including SARS-CoV.